Reproductive health survey, 1997, Jamaica : final report - McFarlane, Carmen; Jamaica. National Family Planning Board ([Kingston, Jamaica] : National Family Planning Board, 1999)
This paper summarizes the findings of the reproductive health survey carried out in Jamaica in 1997 among women aged 15-49 and young adult men aged 15-24. The report aims to provide data on current situations in Jamaica with regards to reproductive health and contraceptive practices. Total fertility rate had been stable in the recent years but declined from 4.5 in 1975 to 2.8 in 1997. It was reported that 39% of the total pregnancies were planned, 43% were mistimed, and 18% were unwanted. For most pregnancies, women had 6 or more visits to prenatal care, and for more than half of pregnancies, women began their prenatal care by the fourth month. Half of the women had had a Pap smear at least once in their lifetime. Women were more likely to have the best knowledge of contraception compared to men. Oral contraceptive was the most prevalent method used by women while men used condom. The main reason for condom use is to prevent pregnancy and sexually transmitted diseases. Sterilized women tended to be older than non-sterilized and tend to be self-selected for their higher parity. Reasons for non-use of contraception vary according to several social and demographic variables. Lastly, results indicate that certain segments of the population are in need of family planning services.
NLJCols20082021
Keywords: Contraception -- Jamaica; Birth control -- Jamaica; Human reproduction -- Jamaica; Fertility, Human -- Jamaica; Health Surveys; Contraception Behavior; Fertility; Health Knowledge, Attitudes, Practice; Jamaica; Birth control; Contraception; Fertility, Human; Human reproduction; Jamaica; Statistics